Simultaneous determination of vitamin E and vitamin K in food supplements using adsorptive stripping square-wave voltammetry at glassy carbon electrode - Kastrati, Gylxhane; Jashari, Granit; Sýs, Milan; Švecová, Blanka; Arbneshi, Tahir; Metelka, Radovan; Bílková, Zuzana; Korecká, Lucie (MDPI, 2020)
A new voltammetric method for the simultaneous determination of vitamin E and vitamin K present in different types of commercially available food supplements has been developed. This electroanalytical method is based on the ex situ adsorptive accumulation of these biologically active compounds onto the surface of a solid glassy carbon electrode (GCE) with subsequent electrochemical detection by square-wave adsorptive stripping voltammetry in 0.01-mol L(-1)HNO(3)containing 0.1-mol L-1KCl at pH 2.08. Due to reversible electrochemical reactions of phylloquinone, a subsequent voltammetric detection of both vitamins in anodic mode can be performed. Since individual forms of vitamins E and K usually exhibit nearly identical electrochemical behavior, it is therefore impossible to distinguish individual forms (quinones and tocopherols) and determine their molar concentrations in this way. Thus, the values of vitamin content were expressed as mass equivalent of phylloquinone and alpha-tocopherol as they are the most biologically active forms. Despite the high sensitivity, relatively short linear ranges were obtained due to the interaction (competition) of both vitamins during adsorption onto the freshly polished surface of the GCE from a 50% aqueous-acetonitrile mixture. The obtained results showed that the voltammetric approach is a very simple and low-cost analytical method that can be used in analyses of food supplements.
Simultánní stanovení vitaminu E a vitaminu K v doplňcích stravy pomocí adsorpční stripping square-wave voltametrie na elektrodě ze skelného uhlíku
Keywords: vitamin E; vitamin K; adsorptive stripping voltammetry; glassy carbon electrode; food supplements; vitamin E; vitamin K; adsorptivní stripping voltametrie; elektroda ze skelného uhlíku; doplňky stravy